Surveillance of antibiotic sensitivity pattern in chronic suppurative otitis media of an Indian teaching hospital - Mahesh Chandra Sahu (KeAi Communications Co., Ltd., 2019)
Introduction: Chronic suppurative otitis media (CSOM) is a common problem in worldwide and untreated CSOM leads to fatal complications like facial nerve paralysis, lateral sinus thrombosis, labyrinthitis, meningitis and brain abscess in developing country like India. Objective: To isolate causative bacteria and antibiotic sensitivity pattern for CSOM and to know the prevalence of extended spectrum beta lactamases (ESBL) and Metallobetalactamases (MBL) in CSOM patients. Methods: A total of 500 ear swabs of clinical suspected CSOM patients were cultured on specific cultured medium and identified the bacteria with conventional methods. Then all the identified bacteria were subjected with specific antibiotics by the Kirby–Bauer's method to know the resistance pattern of antibiotics. ESBL and MBL strains were detected by double disc diffusion test. Results: A total of 384 bacteria were isolated from 500 CSOM patients, among them 86 P. aeruginosa (22.40%), 112 Staphylococcus aureus (29.17%), 53 A. baumannii (13.80%), 32 E. aerogenes (18%), 26 C. freundii (6.77%), 24 K. oxytoca (6.25%), 23 P. vulgaris (5.99%), 18 K. pneumoniae (4.69%) and 10 P. mirabilis (2.60%) identified with conventional methods. From antibiotic disc diffusion methods 74.22% ESBL strains and 9.90% MBL strains were documented. Multidrug resistant strains of P. aeruginosa (86/384,22.40%) were more prevalent than those of S. aureus (112/384,29.17%) and other bacteria in ear discharges. Imipenem and vancomicin could control to gram negative bacteria and gram positive bacteria respectively. Conclusion: Continuous and periodic evaluation of microbiological profile and antimicrobial sensitivity pattern of bacterial is essential for optimum management of CSOM patients. Keywords: Antibiotics, Chronic suppurative otitis media, Gram negative bacteria, ESBL, MBL